36.7k views
3 votes
What is the solution to the following system of equations?

x - 2y = 6

y = 11 - 3x

User LundinCast
by
4.1k points

2 Answers

2 votes

Answer:

x=4 y=-1

Explanation:

x-2(11-3x)=6

x-22+6x=6

7x-22=6

7x=22+6

x=28/7

x=4

-----------------------------

y=11-3(4)

y=11-12

y=-1

User Harambe
by
5.1k points
7 votes

Answer:

(4, -1)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define systems

x - 2y = 6

y = 11 - 3x

Step 2: Rewrite systems

  1. Define: x - 2y = 6
  2. Add 2y on both sides: x = 2y + 6

x = 2y + 6

y = 11 - 3x

Step 3: Solve for y

  1. Substitute in x: y = 11 - 3(2y + 6)
  2. Distribute -3: y = 11 - 6y - 18
  3. Combine like terms: y = -6y - 7
  4. Add 6y on both sides: 7y = -7
  5. Divide 7 on both sides: y = -1

Step 4: Solve for x

  1. Define: x - 2y = 6
  2. Substitute in y: x - 2(-1) = 6
  3. Multiply: x + 2 = 6
  4. Subtract 2 on both sides: x = 4
User Jeckep
by
5.2k points